MySejahtera App and Privacy Concern: A Maqasid Perspective - Muhsin, Sayyed Mohamed; Mughal, Muhammad Junaid (International Institute for Halal Research and Training (INHART), IIUM, 2021)
Amid privacy concerns and cyber security, a conflict of interest is noted in the use of the MySejahtera app as the importance of mass surveillance clashes with protection of individual privacy. In maqāṣidic parlance, it can be portrayed as per the aspect of protection of life (ḥifẓ al-nafs) appears conflicting with the objective of protection of dignity and privacy (ḥifẓ al-ʿirḍ wa al-sirr). However, the Maqāṣid al-Sharīʿah and Qawāʿid al-Fiqhiyyah explain the methods to overcome the conflicting situations and draws the line that where the privacy is breached, there it mandatorily needs to be minimized as much as possible. This study seeks to explore these dimensions, seeing the exigencies on the ground and streamlining maqāṣidic principles as juristic guidance. It finds out that present and future use of the MySejahtera needs to be cautiously arranged in order to prevent the otherwise potential threats it poses to the fundamental rights of citizens.